2018
DOI: 10.1016/j.ajpath.2018.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Splicing Regulatory Protein 1 Inhibits the Invasion and Metastasis of Lung Adenocarcinoma

Abstract: Despite the development of various treatments, metastasis remains a significant problem with lung adenocarcinoma (ADC). The role and mechanism of epithelial splicing regulatory protein 1 (ESRP1), an epithelial-specific RNA binding protein, on promoting the invasion and metastasis of lung ADC remain to be fully elucidated. Immunohistochemical analysis in 125 human lung ADC tissue samples demonstrated that ESRP1 overexpression was inversely related to the presence of metastases, tumor size, and clinical stage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 32 publications
3
17
0
Order By: Relevance
“…ESRP-1 expression decreases during the EMT as cells transition from an epithelial state to a mesenchymal state, suggesting that patient iNCCs had remained in a more epithelial state than both mother and unrelated control iNCCs by 120h differentiation [76,77]. The significantly higher ESRP-1 expression in patient iNCCs was in agreement with the findings that patient iNCC cells had not differentiated to the same extent as the mother and unrelated control iNCC cells by 120h.…”
Section: Mis-splicing In Bmks Patient Inccssupporting
confidence: 82%
“…ESRP-1 expression decreases during the EMT as cells transition from an epithelial state to a mesenchymal state, suggesting that patient iNCCs had remained in a more epithelial state than both mother and unrelated control iNCCs by 120h differentiation [76,77]. The significantly higher ESRP-1 expression in patient iNCCs was in agreement with the findings that patient iNCC cells had not differentiated to the same extent as the mother and unrelated control iNCC cells by 120h.…”
Section: Mis-splicing In Bmks Patient Inccssupporting
confidence: 82%
“…In colon as well as head and neck squamous cell carcinoma, the downregulation of ESRPs is associated with EMT, but there are also reports that show a correlation between ESRP expression and poor survival of patients especially with breast cancer (Shapiro et al, 2011;Yae et al, 2012;Ishii et al, 2014). Recently, Li et al demonstrated an impaired expression of ESRP1 in lung adenocarcinoma and correlated this with alternatively spliced CD44 forms and enhanced EMT (Li et al, 2018).…”
Section: Introductionmentioning
confidence: 95%
“…E-cadherin, and N-cadherin and vimentin are representative markers in epithelial cell and mesenchymal cell, respectively. They have positive correlation among expression of ESRP1, E-cadherin, and N-cadherin ( Supplementary Figure 8) (16). In conclusion, ESRP1 is an important factor that directly affects genes that regulate the epithelial-mesenchymal transition (EMT) and promote prostate cancer invasion and metastasis ( Supplementary Figure 9).…”
Section: A B Cmentioning
confidence: 85%